Aspectos jurídicos do (contra)monumento: por entre preservação e destruição - Magalhães, Bianca Regina Ramos (2023)
Over the past years, a new wave of social movements contesting monuments, related to the struggle for memory, has erupted around the western world, bringing on, in general, the obliteration or the originality demotion of urban works of art. On this subject, this research aim to analise the intentional destruction of public monuments, notably regarding to the legal responses in face of conflicts that arise from the voluntary destruction of city iconography. Essential concepts to delineate the objective of this research are explored, such as the definition of monument and countermonument, emphasizing the indissociability between the urban art study and it’s space-time context; as well as a mapping of the reasons that lead to voluntary damage. Furthermore, the main outcomes provided by spanish and US rights are examined, dialoging them with the nowadays approach of the subject in the brazilian legal system. The purpose is to investigate which answers that the legal science can provide to the clash between international human rights law and cultural heritage law, providing the safeguard of monuments in the atmosphere of the cities – living structures, naturally susceptible to the dynamics of political conflicts – and, in this bias, contributing to the public harmony. Therefore, a qualitative approach is used, based on documentary and bibliographical procedures, with an explanatory purpose, looking to elaborate an applied research. In the end, it is seen that the conclusions achieved are varied, because that logic is permeated by non-unanimity and intersections, but, certainly, an important strategy that has been settled is the resignification of the monument as an antimonument, since it reaches the maximization of the potential of the artistic work, even when it was assaulted or considered aggressive.